(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article explores two fundamental texts of Chilean poetry of the 80s: Diego Maquieira´s La Tirana and Tomás Harris´s Cipango in (neo) baroque code, to suggest the redefinition of some of their most representative problematics. These are texts that stress the idea of representation by means of cross-dressing, the baroque costume in the first case, and the deceitfulness of the senses in the second, in the context of a discussion of historical temporality and authoritarianism.